ax + ay + b(x+y) = a(x + y) + b(x + y) = (a + b)(x + y)
xz + yz - 2xt - 2yt = z(x + y) - 2t(x + y) = (z - 2t)(x + y)
ax² - ay² - bx² - cx² + by² + cy² = a(x² - y²) - b(x² - y²) - c(x² - y²) = (a - b - c)(x² - y²) = (a - b - c)(x - y)(x + y)
a⁴ - a³ + a - 1 = a³(a - 1) + 1(a - 1) = (a³ - 1)(a - 1) = (a - 1)(a - 1)(a² + a + 1)
x² - y² + yz + xy + xz - xy = (x - y)(x + y) + y(z + x) + x(z - y) = (x + y)(x - y + z)
(a+b+c)³-a³ - b³ - c³ = 3a²b + 3a²c + 3ab² + 6abc + 3ac² + 3b²c + 3bc² = 3(a + b)(a + c)(b + c)
Пошаговое объяснение:
1. 3(х+3)-3(4-х)-х-3 = 3x + 9 - 12 + 3x - x - 3 = 5x - 6
2. 3(х+5)-(4-х)-(1+3)х-3 = 3x + 15 - 4 + x - 4x - 3 = 8
3. 2(х+4)-3(2-х)-х-4 = 2x + 8 - 6 + 3x - x - 4 = 4x - 2
4. х+1-5(2-х)-(5+1)х-5 = x + 1 - 10 + 5x - 6x - 5 = -14
5. х+3-(2-х)-х-4 = x + 3 - 2 + x - x - 4 = x - 3
6. 4(х+3)-(5-х)-х-4 = 4x + 12 - 5 + x - x - 4 = 4x + 3
7. 3(х+3)-4(1-х)-(4+3)х-1 = 3x + 9 - 4 + 4x - 7x - 1 = 4
8. 5(х+5)-3(3-х)-х-3 = 5x + 25 - 9 + 3x - x - 3 = 7x + 13
9. 2(х+2) – 5(2-х)-(5+2)х-1 = 2x + 4 - 10 + 5x - 7x - 1 = -7
10. 2(х+4)-4(5-х)-(4+2)х-3 = 2x + 8 - 20 + 4x - 6x - 3 = -15
лучше всего прямые мне так кажется